SEXUALITY AS SEEN IN MAYA ANGELOU'S POEMS, “WOMAN ME”, “PHENOMENAL WOMAN”, AND “SEVEN WOMEN'S BLESSED ASSURANCE” - Ashika Prajnya Paramita (Lexicon, 2012)
Maya Angelou’s poems entitled “Woman Me”, “Phenomenal Woman”, and “Seven Women’s Blessed Assurance” present a topic of woman’s captivating and overwhelming sexuality and beauty that draw men toward her. Using the expressive approach, these poems are studied and analyzed to reveal Angelou’s ideas and perspective of women’s sexuality. In contrast to Angelou, the women in her poems are very confident about themselves. They accept their physical traits, proud of the way they look, and manage to make it their strong point, defining themselves as very strong, confident women. Through her poems, Angelou represents the idea of sexuality completely the opposite of what she was like in her younger years.